EMS induced in vitro mutagenesis for solid mutant induction and validation of mutants using morphological and molecular tools in kinnow mandarin (Citrus nobilis × Citrus deliciosa) - MURUGAN, THEIVANAI; AWASTHI, OM PRAKASH; CHELLAPILLA, BHARADWAJ; SHANKAR, KRIPA (The Indian Journal of Agricultural Sciences, 2024)
Non-chimeric regeneration via in vitro mutagenesis is one of the niche areas in perennial fruit crops to shorten the breeding cycle. However, the recovery of M1 population is a major hurdle due to lack of efficient protocols. Hence the present experiment was conducted during 2021–23 at ICAR-Indian Agricultural Research Institute, New Delhi on EMS induced in vitro mutagenesis and its validation in kinnow mandarin (Citrus nobilis Loureiro × Citrus deliciosa Tenora). The specialized direct somatic embryogenesis (DSE) protocol was standardized and the optimized explants (in ovulo nucellus) were treated with 3 EMS concentration of 0.1, 0.5 and 1.0% for 1, 3 and 5 h. Based on explant survival, probit analysis was calculated and results revealed that the LD50 for in ovulo nucellus explants was 0.3% for 5 h. For a dose rate higher than LD50 i.e. E8 (0.5% for 5 h) and as compared to control, the embryogenesis efficiency was reduced to 65%, likewise embryo production (23.64%), germination (46.15%), conversion (22.76%), establishment (25.85%) and acclimatization (19.44%) showed reducing trend. The EMS derived M1 population showed variability both at morphological and molecular level. Among the markers tested, random amplification of polymorphic DNA (RAPD) and simple sequence repeats (SSR) could demarcate the mutants from mother plant. The origin of homohistont was confirmed from the morphology of observed chlorophyll defective mutants. Thus the optimized EMS dose using DSE system can be effectively used for production of trait specific solid mutants and the morphological and molecular screening protocols have practical value in early selection of M1 population.